Empowering Putra Mangun Jaya F. C. with Data Analysis from Mangunjaya Watch - Suryanto, Tri Lathif Mardi; Wibowo, Nur Cahyo; Nuryananda, Praja Firdaus (Nusantara Science and Technology Proceedings, 2023)
Football is one of the most popular sports in Indonesia. The love of Indonesians for football can be seen from the many soccer clubs throughout Indonesia, ranging from clubs at the national level to clubs at the local level in every city and village, one of which is the Putra Mangun Jaya Football Club. Putra Mangun Jaya Football Club is a football team located in Kediri Regency, East Java, led by Mr. Suharyoko as the Main Director. This article summarizes the authors' activities in conducting market research on data needs for the Putra Mangun Jaya amateur football club and describes how Putra Mangun Jaya collaborated with the authors to become one of the regional amateur clubs that has data analysis as a basis for player development and policy making. The author has developed the Mangunjaya Watch digital application, which is a watch technology that can be used by football players at Putra Mangun Jaya to detect the players' physical endurance or what is called a performance record player. This technology also has the potential to make Putra Mangun Jaya branded as the only regional amateur club with digital data-based analysis. It is hoped that this will provide encouragement to Putra Mangun Jaya to develop further.